Hydrocarbon loads from street cleaning practices: Comparison with dry and wet weather flows in a Parisian combined sewer system - Gasperi, J.; Rocher, V.; Moilleron, R.G.; Chebbo, G. (Polycyclic Aromatic Compounds, 2005)
So far little attention has been given to the effect of the street cleaning waters (SCW) load on the sewer systems during dry-weather periods. However the knowledge of this pollution is needed to better understand the contribution of SCW to dry weather flow (DWF) pollution within combined sewers. Therefore, hydrocarbon loads conveyed by SCW were, analyzed for two different sites of the Paris agglomeration. Median n-alkane, Unresolved Complex Mixture (UCM) and Polycyclic Aromatic Hydrocarbon (PAH) concentrations have been estimated at 19, 628 and 1.4 mu g (.) l(-1) for the Marais catchment (or 4th district), and at 8, 249, and 2.1 mu g (.) l(-1) for the 13th district, respectively.